RESTROSPEKSI PENCIPTAAN KARYA TARI SLEWAH - Cahyana, Juz Tsani; MD, Slamet (Universitas PGRI Palembang, 2025)
This research aims to reveal or describe reproduction, namely looking at events that have been exceeded from the process of creating Slewah dance works. This research has the problem of how the form of the Slewah dance work and the process of creating the Slewah dance work. Answering the problem of the form of the Slewah dance work using the theory of Slamet MD, while answering the problem of the process of creating the Slewah dance work using the theory of Alma Hawkins translated by Y. Sumandiyo Hadi. The method used in this study uses a qualitative method research type with a choreographic approach. Data collection techniques include observation, interviews, and literature studies.The results of the study show that reintrospection, namely looking at the past or looking back at the creation process that has occurred so that the creation of Slewah dance works which includes the form of Slewah dance works and the process of creating Slewah dance works. The form of Slewah dance works discusses 1) movement, 2) dancers, 3) fashion makeup, 4) floor patterns, 5) dance music, and 6) performance venues. The process of creating Slewah dance works discusses 1) exploration, 2) improvisation, and 3) composition. Keywords: Slewah Dance; Form; Creation Process.